PHYSIOTHERAPY PROGRAM PHASE 1 POST RECONSTRUCTION ACL CONDITIONS: A CASE STUDY - Nur'ana, Hafiz Arief; Sudaryanto, Wahyu Tri; Fandrian, Ganang (Universitas Muhammadiyah Surakarta, 2021)
Introduction: The incidence of ACL Rupture ranges from 30 to 78 per 100,000 people per year, after ACL reconstruction 61% to 89% of athletes successfully return to sport, usually 8 to 18 months after reconstruction. In the management of cases of ACL tear, reconstruction of the ACL ligament will be carried out with the procedure of grafting the ACL with tendon tissue to restore the stabilizing function of the ACL ligament in the knee joint. Case Presentation: A 19-year-old male patient with a post ACL reconstruction diagnosis, with complaints of pain in the patient's knee, difficulty bending the knee, and decreased muscle strength in the leg after ACL reconstruction. Management and Outcome: The patient participated in 6 therapies, in 1 therapy for 60 minutes for 2 weeks, with a physiotherapy program in the form of giving Ice compression, ROM exercise, and Strenghtening exercise. And in the evaluation, several measurements were carried out, namely pain measurements using NRS, measurements of muscle strength using MMT, and also measurements of Range of Motion using a goniometer. Discussion: The Physiotherapy program carried out in phase 1 of post-ACL rehabilitation is aimed at reducing pain and edema, increasing the range of motion of the joints, and also strengthening muscles before moving on to the next stage/phase. reduce the intensity of inflammation in the tissue, ROM Exercise which aims to maintain or improve joint mobility and can also increase muscle mass and muscle tone, in addition to maintaining the mobility of the joint and to minimize a decrease in the elasticity of the tissue around the joint, and Also doing strengthening exercises to strengthen the muscles around the knee to increase stability in the knee joint. Conclusion: Post-ACL rehabilitation physiotherapy program using MOON Guideline in Phase 1 Rehabilitation with Ice Compression, ROM Exercise, and also Strenghthening Exercise can reduce pain, increase muscle strength and can improve the functional ability of patients after ACL reconstruction.